Diversidade e ecologia das raias de água doce (chondrichthyes: potamotrygonidae) da Reserva Biológica do Parazinho, AP - Gama, Cecile de Souza (2013)
Freshwater stingrays of the Potamotrygonidae family are restricted to South America, where they occur in the main river systems. This is the only group within Elasmobranchs that is exclusive to freshwater, thus, presenting morphological and physiological adaptations to this particular environment. In some regions these animals usually have a strong presence in the lifestyle of riparian populations, because of their high potential for accidents with humans. The present study was conducted at the Parazinho Biological Reserve, an island in the archipelago of Bailique, Macapá (AP), located at the mouth of the Amazon River. The study evaluated the composition and structure of freshwater stingray species by determining the taxocenose population contingent and understanding their biological and ecological characteristics such as feeding habits, reproduction, movement, and morphological features. Additionally, their spatial habitat patterns on the island were examined. Samplings were performed bimonthly between March 2011 and January 2013. Longlines, fishnets and spears were used to capture specimens. All specimens collected in the first year were measured and marked with an implanted microchip and subsequently released. In the second year, the captured stingrays were preserved and dissected to analyze their gonads and digestive tracts. A total of 223 animals were caught during the 82 days of sampling, corresponding to 208 different specimens of stingrays. Eight species were identified: Paratrygon aiereba, Potamotrygon motoro, P orbignyi, P. scobina, P. constellata, P. cf. dumerilii, Potamotrygon sp., and Potamotrygon sp. 1. Discriminant analysis between the ratio of the disk width and morphometric data of the most representative species (Potamotrygon cf. dumerilii, P. motoro, P. orbignyi, P. scobina, and Potamotrygon sp. 1) revealed dimensional differences among species, although these did not reach significant levels in most cases. The population study revealed that the distribution of stingrays by gender was homogeneous, and no habitat preference by species was observed along the island. Weight length relationship analysis showed that males and females have different growth patterns; however, the differences were small and not significant (α = 0.05). The analysis of 95 stomachs confirmed predatory activity. The main food source consisted of invertebrates, predominantly crustaceans, mollusks, insects and annelids. The analysis also revealed differences in the consumption of prey throughout the year and among species. It was observed that freshwater stingrays are specialist fish with low niche width, indicating overlaps between spatial movements and dietary patterns based on the availability of food resources in the environment. The animals reproduced throughout the year, following alternate reproductive periods. The observed overlap of reproductive periods among species is indicative of possible hybridization. The study also showed that freshwater stingrays are conservative with regard to site utilization.